Exploring a food is medicine pilot program to improve dietary quality among rural perinatal patients - Sophia E. Allen; Taralyn Bielaski; Chelsey R. Canavan (BMC Nutrition)
Abstract Background Food insecurity and other unmet social needs can contribute to adverse outcomes for mothers and newborns. Food is Medicine (FIM) approaches are promising for improving nutrition and preventing chronic disease but have not been explored fully among rural-dwelling pregnant people. Our objectives were to (1) assess the potential of FIM programs to improve perinatal dietary quality; (2) assess patient satisfaction and self-reported health status with various FIM options; and (3) identify barriers to healthy eating among rural perinatal patients experiencing food insecurity. Methods Pregnant patients identified via a validated screener as experiencing food insecurity were referred to a community health worker (CHW), offered nutrition education, and connected to one or more FIM supports. A range of FIM programs developed through clinic-community partnerships provided tailored support to meet individual patient needs. We surveyed patients who received FIM support(s) from Dec 2023 - March 2024 regarding their satisfaction with and dietary changes related to FIM support. We collected qualitative data on challenges to healthy eating during pregnancy and opportunities for program improvement. Results In survey responses (n = 31), patients indicated high satisfaction with all FIM supports, especially more intensive options, and reported eating more vegetables, fruits, whole grains, and healthy proteins. 71% indicated a small positive change in diet quality, with home-delivered nutritionally tailored meals most likely to influence a larger positive change. The most common barriers to healthy eating included food preferences or aversions, transportation challenges, poor quality of available food, and limited time to cook or eat. Conclusions We identified strong potential for FIM interventions during pregnancy to improve diet quality and overall health. More research is needed to evaluate the effects of FIM programs on food security and dietary quality during pregnancy and to tailor the type and duration of food support.